Một số flavonoid và dẫn xuất bergenin phân lập từ lá cây cơm nguội đảo Ardisia insularis - Hồng Vân, Nguyễn Thị; Viên, Trịnh Anh; Long, Phạm Quốc; Cường, Nguyễn Mạnh; Anh, Lưu Tuấn (Vietnam Journal of Chemistry, 2015)
From the leaves of Ardisia insularis, six flavonoids and four bergenin derivatives have been isolated, myricitrin (1), myricetin 3-O-(3″-O-galloyl)-α-L-rhamnopyranoside (2), desmanthine-2 (3), quercetin 3-O-α-L-rhamnopyranoside (4), 3-O-galloylepicatechin (5), 3-O-galloyl-3'-methoxyepicatechin (6), bergenin (7), norbergenin (8), demethoxybergenin (9) and 4-O-galloylbergenin (10). The structure elucidation of these compounds was peformed by spectroscopic data ESI-MS, 1D-NMR (1H-NMR, 13C-NMR, DEPT) and 2D-NMR (HSQC, HMBC, COSY).